Crocin promotes ferroptosis in gastric cancer via the Nrf2/GGTLC2 pathway - Yan, Nan; Li, Gaofu; Zhao, Linglin; Guo, Qijing; Yang, Jie; Liu, Jianhong; Zhou, Wei; Gao, Yue; Luo, Yushuang (Frontiers in Pharmacology, 2025)
Introduction: Gastric cancer (GC) is characterized by high incidence and poor survival rates. Crocin, a natural carotenoid from saffron, exhibits antioxidant, anti-inflammatory, and anti-tumor properties. Ferroptosis, an iron-dependent cell death driven by lipid peroxidation, plays a critical role in cancer progression and is a potential therapeutic target. This study investigates whether crocin inhibits GC cell proliferation by inducing ferroptosis and explores its underlying mechanisms.Methods: This study employed in vivo and in vitro models to assess crocin’s effects on GC cell proliferation, apoptosis, migration, invasion, and ferroptosis. Pathway enrichment analysis was performed on differentially expressed genes post-crocin treatment. Lentiviral vectors were used to knockdown and overexpress GGTLC2, exploring its role in GC progression and crocin’s therapeutic effects. The UCSC and JASPAR databases predicted Nrf2 binding sites in the GGTLC2 promoter. Molecular docking evaluated crocin’s affinity for Nrf2 and GGTLC2. Immunofluorescence and nuclear-cytoplasmic fractionation assays analyzed Nrf2 expression and localization. ChIP-qPCR determined Nrf2’s regulatory role on GGTLC2 and crocin’s modulatory effects.Results: The results demonstrated that crocin significantly inhibited the proliferation, migration, and invasion of GC cells while promoting apoptosis. Differentially expressed genes following crocin treatment were predominantly enriched in pathways associated with oxidative stress and ferroptosis. Crocin downregulated the oncogene GGTLC2, thereby suppressing GC cell proliferation, invasion, and migration, while simultaneously promoting apoptosis and ferroptosis. Molecular docking analysis revealed a stable binding affinity between crocin and GGTLC2, suggesting that crocin may directly target GGTLC2 to modulate its expression. Additionally, crocin facilitated the translocation of Nrf2 from the nucleus to the cytoplasm. ChIP-qPCR results confirmed that Nrf2 directly binds to the GGTLC2 promoter region to regulate its expression, and crocin attenuated this binding interaction.Discussion: In conclusion, our findings suggest that crocin, as a promising natural compound for GC therapy, may inhibit ferroptosis in GC cells through the Nrf2/GGTLC2 signaling pathway, thereby suppressing tumor initiation and progression. This study provides novel insights into the molecular mechanisms underlying the anti-tumor effects of crocin and highlights its potential as a therapeutic agent for GC.